Social media marketing strategy : definition, conceptualization, taxonomy, validation, and future agenda - Li, Fangfang; Larimo, Jorma; Leonidou, Leonidas C. (Springer, 2020)
Although social media use is gaining increasing importance as a component of firms’ portfolio of strategies, scant research has systematically consolidated and extended knowledge on social media marketing strategies (SMMSs). To fill this research gap, we first define SMMS, using social media and marketing strategy dimensions. This is followed by a conceptualization of the developmental process of SMMSs, which comprises four major components, namely drivers, inputs, throughputs, and outputs. Next, we propose a taxonomy that classifies SMMSs into four types according to their strategic maturity level: social commerce strategy, social content strategy, social monitoring strategy, and social CRM strategy. We subsequently validate this taxonomy of SMMSs using information derived from prior empirical studies, as well with data collected from in-depth interviews and a quantitive survey among social media marketing managers. Finally, we suggest fruitful directions for future research based on input received from scholars specializing in the field.
Keywords: Customer engagement; Marketing strategy; Social media marketing strategy; social media; fi=Kansainvälinen liiketoiminta|en=International Business|